Cancerous Genome and Mass of Autoinfected Cells, Resulting in Cancer (British Journal of Multidisciplinary and Advanced Studies, 2023)
Cancer is one of the types of genomic diseases. It is caused by pathogenic mutation in the Genome inside a cell so that the cell can be activated to divide & grow uncontrollably. The key objective of this study is to verify that the actual causative agent of the disease cancer is the pathogenic mutation in Genome. The contents of Figures displayed are designed to serve as Results in the targetful strategy of this study. The actual causative agent of cancer and the precancerous effects of risk factors of cancer are identified and made available in order to have strong conclusive statements.  Cancer occurs if and only if Cancerous Genome synthesizes enormous number of autoinfected (cancered) cells rapidly by way of apoptosisless and uncontrolled growth of cancered cells involving fast cell division, using its chemical energy-containing nutrients as raw materials; otherwise, none of the precancerous effects of risk factors of cancer can cause the occurrence of cancer.